Odpowiedzi

2010-03-30T20:41:08+02:00
A) -6+8*(-2)-(-3)-2*(-2)=-6-16+3+4=-22+7=-15
b)-8*(-1)-4*2+0,5-(-1)-4+1=8-8+0,5+1-4+1=1,5-4+1=-2,5+1=-1,5
c)9*3-(7*3+(-2))+(6*(-2)+7*3)=27-(21-2)+(-12+21)=27-19+9=17
2010-03-30T20:44:33+02:00
A)-y+8x-z-2x dla x= -2 , y = 6 , z = -3
-6+8(-2)-(-3)-2(-2)
-6-16+3+4
-22+7=-15
b)- 8y - 4z +x - y - 2z + 1 dla x = 0,5 , y = -1 , z= 2
-8(-1)-4(2)+0,5-(-1)-2(2)+1
8-8+0,5+1-4+1
2,5-4= - 1,5
c) 9y- (7y+x)+(6x+7y) dla x= -2 y = 3
9(3) - (7*3+ -2) + (6* -2+7*3)
27 - 21 +2 + -12 +21
6 +2 + (-12)+21
29+(-12)
17

Chyba tak to powinno być, lecz nie jestem pewna.